Catalytic activity and coke resistance of gasification slag-supported Ni catalysts during steam reforming of plastic pyrolysis gas - Ong, Hang Meng (2023)
Pyrolysis gas from polyolefinic plastic waste is a hydrocarbon-rich feedstock for sustainable syngas production. The effect of Cr, Mo, and W promoters on the activity of gasification slag-supported Ni catalysts during the reforming of plastic pyrolysis gas was investigated (polyethylene and polypropylene mixed feedstock, Ni:promoter molar ratio = 4.5, 800 °C, steam-To-carbon molar ratio of 7). Based on 3 h reforming tests, all catalysts showed stable conversion efficiency, suggesting that gasification slag from municipal solid waste is a promising replacement material for traditionally used alumina supports. Moreover, the slag demonstrated good thermal stability and potential for catalyst recycling, justifying the economic benefit of valorizing the material. Interestingly, interaction between slags and promoters is evidenced by the formation of CaWO4and CaMoO4phases, which may have an impact on the reforming activity of bimetallic catalysts. Among the studied catalysts, the highest conversion efficiency of hydrocarbon compounds (76%), highest H2(122.65 mmol Lfeed-1) and CO (49.34 mmol Lfeed-1) yields, and lowest coke deposition (0.06 wt %) were demonstrated by the Ni-Mo catalyst. The superior performance of Ni-Mo was accompanied by the growth of carbon nanotubes via a tip-growth mechanism, which was not observed in other catalysts. Spherical carbon nanocages and filamentous carbon nanofibers predominated in coke deposits of Ni, Ni-W, and Ni-Cr. The high syngas production efficiency of Ni-Mo could be attributed to the dispersion of metal by the growing carbon nanotubes providing the reaction sites for reforming and coke gasification reactions. Owing to these properties, Ni catalyst promoted by Mo and loaded on a gasification support has high potential for the syngas production from plastic pyrolysis gas.